Season of birth is associated with birth weight, pubertal timing, adult body size and educational attainment: a UK Biobank study. Issue 2 (October 2015) - Day, Felix R.; Forouhi, Nita G.; Ong, Ken K.; Perry, John R.B.
Abstract: Season of birth, a marker of in utero vitamin D exposure, has been associated with a wide range of health outcomes. Using a dataset of ∼450, 000 participants from the UK Biobank study, we aimed to assess the impact of this seasonality on birth weight, age at menarche, adult height and body mass index (BMI). Birth weight, age at menarche and height, but not BMI, were highly significantly associated with season of birth. Individuals born in summer (June–July–August) had higher mean birth weight (P = 8 × 10 −10 ), later pubertal development (P = 1.1 × 10 −45 ) and taller adult height (P = 6.5 × 10 −9 ) compared to those born in all other seasons. Concordantly, those born in winter (December–January–February) showed directionally opposite differences in these outcomes. A secondary comparison of the extreme differences between months revealed higher odds ratios [95% confidence intervals (CI)] for low birth weight in February vs. September (1.23 [1.15–1.32], P = 4.4 × 10 −10 ), for early puberty in September vs. July (1.22 [1.16–1.28], P = 7.3 × 10 −15 ) and for short stature in December vs. June (1.09 [1.03–1.17], P = 0.006). The above associations were also seen with total hours of sunshine during the second trimester, but not during the first three months after birth. Additional associations were observed with educational attainment; individuals born in autumn vs. summer were more likely to continue in education post age 16 years (P = 1.1 × 10 −91 ) or attain a degree-level qualification (P = 4 × 10 −7 ). However, unlike other outcomes, an abrupt difference was seen between those born in August vs. September, which flank the start of the school year. Our findings provide support for the 'fetal programming' hypothesis, refining and extending the impact that season of birth has on childhood growth and development. Whilst other mechanisms may contribute to these associations, these findings are consistent with a possible role of in utero vitamin D exposure.